The role of telomere and telomerase in cancer and novel therapeutic target: narrative review - Baylie, Temesgen; Jemal, Mohammed; Baye, Gelagay; Getinet, Mamaru; Amare, Gashaw Azanaw; Adugna, Adane; Abebaw, Desalegn; Hibstu, Zigale; Tegegne, Bantayehu Addis; Gugsa, Endalkachew; Adane, Tadegew; Getie, Gedefaw; et al. (Frontiers in Oncology, 2025)
Telomeres are dynamic complexes at the ends of chromosomes that are made up of protective proteins and tandem repeating DNA sequences. In the large majority of cancer cells, telomere length is maintained by telomerase, an enzyme that elongates telomeres. Telomerase activation is seen in the majority of cancer, which permits uncontrol cell proliferation. About 90% of human malignancies show telomere dysfunction and telomerase reactivation; as a result, telomerase activation plays a special role as a practically universal stage on the way to malignancy. This review understands the structural and functional of telomere and telomerase, mechanisms of telomerase activation in oncogenesis, biomarkers and therapeutic targets. Therapeutic strategies targeting telomerase, including antisense oligonucleotides, G-quadruplex stabilizers, immunotherapy, small-molecule inhibitors, gene therapy, Telomerase-Responsive Drug Release System, have shown promise in preclinical and clinical settings. Advances in telomere biology not only illuminate the complex interplay between telomeres, telomerase, and cancer progression but also open avenues for innovative, targeted cancer therapies.